DAMPAK BERGABUNGNYA MASKAPAI PENERBANGAN GARUDA INDONESIA DENGAN INTERNATIONAL AIR TRANSPORT ASSOCIATION (IATA) - Wiwid Try Lestari; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research discuss the problems which often faced by the national airline, Garuda Indonesia. As a State-Owned Enterprises in the field of air transportation services, PT. Garuda Indonesia (Persero) Tbk. has an important record of the quality of security and safety standards at the global level due to prohibiting flying tragedy to the skies of Europe in 2007 and decides to join the world air transportation organization, IATA. Until nowadays, Garuda Indonesia is able to maintain the IOSA safety certification issued by IATA.            To analyze these kinds of problem, the author applies qualitative method that  supported by Liberalism Perspective and Group as the level of analysis. The SOE concept that used in this research collaboration with the Globalization theory to analyze the impact.            As a five-star airline, IOSA Certification is the main measure of the quality of safety aspect that created by the airline despite of its flight frequency are wide so that it is adhere with the aviation regulations issued by ICAO. The membership status of Garuda Indonesia with IATA also affects the policies taken by the company internally, such as related to reducing exhaust emissions and also around company's management environmentKeywords: Garuda Indonesia, IOSA, IATA,Safety and Security,ICAO